1971
DOI: 10.1002/anie.197103741
|View full text |Cite
|
Sign up to set email alerts
|

Bis(trimethylsilyl)diimine: Preparation, Structure, and Reactivity

Abstract: Dedicated to my father, Professor Egon Wiberg, on the occasion of his 70th birthdayThe highly reactive compound bis(trimethylsily1)diimine (BSD), which was first prepared by oxidation of lithium tris(trimethylsilyl)hydrazide, is light blue, sensitive to thermolysis and hydrolysis, and ignites spontaneously in air. On the basis of electron transfer, acid-base, or freeradical reactions, it acts in particular as a (preparatively useful) redox system and as an agent for the introduction of azo groups. Redox reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
1

Year Published

1971
1971
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 47 publications
(17 reference statements)
0
5
0
1
Order By: Relevance
“…tBu-N = N-tBu > 200 8C, Ph-N = N-Ph > 600 8C), which even lies below its melting point of about À3 8C. [16,17] Since diazene 2 decomposes at ambient temperatures with a half-time of 7.6 h (zero-order reaction, in a 5:1 mixture of npentane/toluene) it must be kept at temperatures below À50 8C in solution or in the solid state (see Figure S14 in the Supporting Information). [18] A suitable low-temperature synthesis had to be found to generate the tris(trimethylsilyl)diazenium ion [(Me 3 Si) 2 3 Si-X with X = Cl, F; CB = [CHB 11 H 5 X 6 ], X = Br, Cl).…”
mentioning
confidence: 93%
“…tBu-N = N-tBu > 200 8C, Ph-N = N-Ph > 600 8C), which even lies below its melting point of about À3 8C. [16,17] Since diazene 2 decomposes at ambient temperatures with a half-time of 7.6 h (zero-order reaction, in a 5:1 mixture of npentane/toluene) it must be kept at temperatures below À50 8C in solution or in the solid state (see Figure S14 in the Supporting Information). [18] A suitable low-temperature synthesis had to be found to generate the tris(trimethylsilyl)diazenium ion [(Me 3 Si) 2 3 Si-X with X = Cl, F; CB = [CHB 11 H 5 X 6 ], X = Br, Cl).…”
mentioning
confidence: 93%
“…Early endeavors demonstrated that the stability of the parent diimide is significantly increased by replacing the hydrogen atom by a silyl group . In this context, Wiberg originally isolated bis­(trimethylsilyl)­diazene (Me 3 Si–NN–SiMe 3 ) as a light blue liquid, displaying both an improved thermal stability and reactivity in comparison to its hydrogen-substituted counterpart . In line with these findings, aryl- and alkyl-substituted silyldiazenes (R–NN– Si , R = aryl or alkyl and Si = triorganosilyl) were shown to be kinetically stable precursors but their synthetic applicability has been far less investigated in part owing to the lack of general strategies for their synthesis. In 1964, Wannagat and Krüger isolated the deep blue phenyl- and tolyl-substituted diazenes capped with a range of silyl groups through bis-lithiation and further oxidation of the corresponding silylated hydrazines 7 (Scheme , eq 1). , Later, Watanabe and co-workers developed a procedure for the dehydrogenation of silyl-substituted phenylhydrazines, making use of the oxidizing agent di- tert -butylperoxide ( 8 ) at elevated temperatures, delivering the corresponding azo compounds in moderate yields (Scheme , eq 2) .…”
Section: Introductionmentioning
confidence: 91%
“…9 In this context, Wiberg originally isolated bis(trimethylsilyl)diazene (Me 3 Si−N�N−SiMe 3 ) as a light blue liquid, displaying both an improved thermal stability and reactivity in comparison to its hydrogen-substituted counterpart. 10 In line with these findings, aryl-and alkyl-substituted silyldiazenes (R−N�N−Si, R = aryl or alkyl and Si = triorganosilyl) were shown to be kinetically stable precursors but their synthetic applicability has been far less investigated in part owing to the lack of general strategies for their synthesis. 11−15 In 1964, Wannagat and Kruger isolated the deep blue phenyl-and tolyl-substituted diazenes capped with a range of silyl groups through bis-lithiation and further oxidation of the corresponding silylated hydrazines 7 (Scheme 2, eq 1).…”
Section: Introductionmentioning
confidence: 99%
“…In 1968, Wiberg and co-workers isolated and studied the light blue, thermolabile trans -bis­(trimethylsilyl)­diazene (BSD, Me 3 Si–NN–SiMe 3 ), which is comparatively more stable than the corresponding diimide ( t 1/2 = 7.6 h versus a few seconds at room temperature) but shares common reactivity patterns with the latter . The synthesis and the properties of N -aryl- N ′-silyldiazenes (Ar–NN–SiR 3 ) have been comparatively less studied.…”
Section: Introductionmentioning
confidence: 99%